Tunable thermal properties of the biphenylene and the lateral heterostructure formed with graphene: A molecular dynamics investigation - Cui, Qiang; Ren, Kai; Zheng, Ruxing; Zhang, Qiuhua; Yu, Luxin; Li, Jianping (Frontiers in Physics, 2022)
Recently, biphenylene was successfully synthesized as a novel allotrope of carbon. In this investigation, non-equilibrium molecular dynamics calculations are conducted to explore the intrinsic thermal properties of biphenylene. The isotropic thermal conductivity of biphenylene is obtained, which is also sensitive to size and temperature. Furthermore, the graphene/biphenylene lateral heterostructure is constructed to possess an interfacial thermal conductance of about 2.84 × 109 W K−1 m−2. The external tensile strain can induce a redshift of the vibrational density of states of pristine graphene and biphenylene, and the improved overlap also results in an enhanced heat flux in the biphenylene/graphene heterostructure. Our approach can provide theoretical guidance to design a thermal management device based on graphene and biphenylene.